Psychological distress and its associated risk factors among university students - Li,Tingting (2020)
SUMMARY OBJECTIVE Psychological distress is an important mental health problem among university students. The goal of this study was to determine psychological distress and its associated risk factors among students in the Anhui province. METHODS A cross-sectional study was conducted in a sample of 1304 students. In this study, a self-administered questionnaire consisting of the general demography and General Health Questionnaire (GHQ-12) was completed. Psychological distress was assessed using the GHQ-12-item questionnaire. A dichotomous category split was imposed on the GHQ-12 for the purpose of analysis. A GHQ-12 score of 4 or higher indicated psychological distress. The data were analyzed by SPSS 20.0 system. RESULTS A total of 1304 samples were analyzed in this study. The results indicated that the education level of the father and mother was associated with the students’ psychological distress (P<0.001). A significant association was found between high-intensity exercise and low-intensity exercise and psychological distress. However, no significant difference was identified between gender and psychological distress (P=0.173). CONCLUSION The education level of parents, high-intensity exercise, and low-intensity exercise were associated with psychological distress. Our results suggest that it is indispensable to raise awareness of psychological disorders and its associated risk factors among university students. Further studies are required to develop appropriate interventions for high-risk groups.